Konsep Tarbiyah Menurut Ibnu Taimiyyah: Studi Filosofis tentang Fondasi Keimanan, Akhlak, dan Pembiasaan dalam Pendidikan Islam - Adi Kusmanto; Nasrulloh; Maftuh; Hartoyo (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2026)
This study examines the concept of tarbiyah in the educational thought of Ibn Taymiyyah and analyzes its philosophical foundations within the broader context of Islamic intellectual history. Using a qualitative library research design, the study analyzes key primary texts, particularly Majmu‘ al-Fatawa and Kitab al-Iman, alongside relevant contemporary scholarship. The findings reveal that Ibn Taymiyyah’s concept of tarbiyah constitutes an integrative educational model grounded in tawhid, moral character formation (akhlaq), and habituation as a practical mechanism for ethical development. Unlike approaches that emphasize mystical or speculative dimensions of education, his framework is rooted in scriptural authority and practical moral discipline, reflecting a critical stance toward speculative theology (kalam). This study argues that Ibn Taymiyyah’s educational thought offers a coherent philosophical framework that integrates theological belief, ethical formation, and social practice. Theoretically, it contributes to the reconceptualization of Islamic education as a holistic system that connects faith, knowledge, and action. Practically, the framework provides insights for contemporary Islamic education, particularly in developing value-based curricula, character education, and holistic assessment models that integrate cognitive, moral, and spiritual dimensions.